Alternative sources of protein in milk replacers for calves: a review - Campos, Oriel F. de; Silva, Aliomar G. (Pesquisa Agropecuaria Brasileira, 2014)
It was reviwed the literature data in the alternative sources of protein used to prepare calves milk replacers. Among several feedstuffs, the soybean and the fish have been more intensivelly studied. It may be due to their disponibilities and prices. Bacterial sludge, meat and blood solubles, fababean, colza and alfalfa have been less intensivelly studied. One of the biggest problems to compare the literature results is the kind and quality diversities of soybean of fish products used. Several researchs have shown a clear composition and nutritive value differences among different products used to feed calves. This review has summarized the performance of calves fed different kinds of protein sources. It can be concluded that a decreasing calves performance can be expected when the amount of alternative protein is increased in the milk replacer. It is more evident when the milk replacer has a lower level of total protein or when the replacer is the main source of nutrients. It is without doubt that the improvement in commercial milk replacers depend on the progress in the know how the soybean and fish manufacture.